Tailings storage facilities flood exposure assessment using a 2D hydrodynamic model. Issue 3 (17th May 2022) - Murillo, Gabriel Perez; McIntyre, Neil; Cohen, Raymond C. Z.; Prakash, Mahesh
Abstract: Minimizing environmental pollution from Tailings Storage Facilities (TSFs) is one of the key goals of the mining sector. While much attention is given to risks from potential catastrophic failures of large TSFs, there is also a need to assess risks due to noncatastrophic but more frequent releases of contaminants. In response to this need, this article proposes a method for prioritizing TSFs in terms of flood exposure, based on flood maps produced by the Shallow Water Integrated Flood Tool. The method was implemented using a case study of a flood event in the Copiapó city region (Atacama, Chile). A sensitivity analysis was carried out to evaluate the influence of different model configurations and input parameters. The results showed that 10% of all the TSFs in the case study region were exposed to flood waters due to the fluvial dynamics of the Copiapo River. Additionally, the sensitivity analysis revealed that in the event of extreme local precipitation, capable of generating runoff, up to 88% of all the TSFs could have some degree of flood exposure. The results also suggest that flood simulations using satellite‐derived terrain data at moderate resolution can be used for a preliminary large‐scale assessment of TSF flood exposure.